Comparative Analysis of the Bioactive Compounds in Chicken Cartilage: Protective Effects of Chondroitin Sulfate and Type II Collagen Peptides Against Osteoarthritis Involve Gut Microbiota - Zhang, Hongru; Qi, Liwei; Shen, Qingshan; Wang, Ruiqi; Guo, Yujie; Zhang, Chunhui; Richel, Aurore (Frontiers in Nutrition, 2022)
This study was designed to explore osteoarthritis (OA) treatment from bioactive compounds of chicken cartilage food supplements. The OA rat model induced by sodium iodoacetate was used to evaluate the treatment effect in vivo. Here, we used animal experiments to show that oral chondroitin sulfate (CS), cartilage powder, and type II collagen peptides could increase the athletic ability of rats and reduce inflammatory cytokine levels in serum or synovial fluid, including prostaglandin E2, tumour necrosis factor-α, interleukin 1β, interleukin 6, and interleukin 17. CS displayed the best treatment effect against OA. The morphological structure of articular cartilage indicated that CS could significantly improve cartilage tissue morphology and reduce OA score. Oral CS slowed down the development of OA by modulating gut microbiota. These results provided a useful scientific basis for the high-value utilization of chicken cartilage.